ELAZIĞ VE ÇEVRESİNDEKİ SIĞIRLARIN KAN PLAZMASI, ALKALİN FOSFATAZ VE KIL ÇİNKO DEĞERLERİ ÜZERİNDE ARAŞTIRMALAR - ÇİMTAY, İBRAHİM (Fırat Üniveristesi, 1996)
Bu çalışma, Elazığ ve çevresindeki Holştayn ve Montafon ırkı sığırlarda subklinik çinko yetersizliğinin araştırılması için kan plazması çinko, alkalin fosfataz ve kıl çinko düzeylerinin incelenmesi, anılan parametreler üzerinde ırk, iklim, gebelik, laktasyon ve kıl değişiminin etkilerinin değerlendirilmesi, plazma çinko ve plazma alkalin fosfataz ile plazma çinko ve kıl çinko düzeyleri arasında hangi yönde bir ilişkinin bulunduğunun saptanması amacıyla yapılmıştır. Araştırmada, Elazığ Merkez İlçe'ye bağlı Alaca, Harmantepe, Sinan, Bağdere, Güneyçayırı ve Altınçevre köyleri ile Fırat Üniversitesi Araştırma ve Uygulama Çiftliği'nden temin edilen 12 aylıktan büyük dişi sığırlar kullanılmıştır. Araştırma sığırlarının kan ve kıl örnekleri Aralık 1994, Mart, Haziran ve Eylül 1995 aylarında toplanmıştır. Çalışmada Aralık ayında 56 adet Holştayn ve 47 adet Montafon olmak üzere toplam 103 baş sığır, Mart ayında 56 adet Holştayn ve 46 adet Montafon olmak üzere toplam 102 baş sığır, Haziran ayında 64 adet Holştayn ve 40 adet Montafon olmak üzere toplam 104 baş sığır, Eylül ayında ise 65 adet Holştayn ve 38 adet Montafon olmak üzere toplam 103 baş sığır kullanılmıştır. Kan örneklerinin plazmaları ayrılarak çinko ve alkalin fosfataz, kıl örneklerinde çinko düzeyleri ölçülmüştür. Araştırmada plazma çinko ortalamaları; Aralık ayında 108,90 ± 2,26 //g./dl., Mart ayında 99,67 ± 2,16 //g./dl., Haziran ayında 104,51 ± 2,26 jMg./dl. ve Eylül ayında 103,25 ± 1,71 /

This study was conducted with an aim to examine the levels of blood plasma zinc and alkaline phosphatase and the levels of hair zinc in order to determine the subclinical zinc deficiency in Swiss Brown and Holstein cattle in Elazığ and its surrounding areas, to evaluate the effects of breed, climate, gestation, lactation and physiological hair shedding on these parameters and to determine what sorts of relationships present between plasma zinc and alkaline phosphatase concentrations, between plasma and hair zinc concentrations. Female cattle that were aged than 12-months-old and bred in farms of some Elazığ villages called Alaca, Harmantepe, Sinan, Bağdere, Güneyçayırı and Altınçevre and in The Research and Application Farm of University of Fırat were used. The blood and hair samples of the cattle used in the study were collected in December 1994, in March, June and September 1995. In the present study, it has been used 56 Holstein and 47 Swiss Brown in December, 56 Holstein and 46 Swiss Brown in March, 64 Holstein and 40 Swiss Brown in June and 65 Holstein and 38 Swiss Brown in September. Zinc and alkaline phosphatase levels of the blood plasma samples and zinc levels of the hair samples were measured. In the current study mean zinc levels of the plasma were found to be 108.90 ± 2.26 pig/dl in December, 99.67 ± 2.16 jtg/dl in March, 104.51 ± 2.26 fig/dl in June and 103.25 ±1.71 //g/dl in September. A significant difference ( p<0.05 ) was found in mean plasma zinc levels between December and March. Mean levels of alkaline phosphatase were found to be 84.23 ± 6.31 IU/L in December, 71.64 ± 4.61 IU/L in March, 72.09 ± 3.87 IU/L in June and 56.24 ± 2.99 IU/L in September. Mean alkaline phosphatase levels were found64 to be significantly ( p<0.01 ) different between December and September. Mean hair zinc levels were found to 87.47 ± 1.11 ppm, 108.19 ± 1.33 ppm, 90.87 ± 1.50 ppm and 85.71 ± 1.46 ppm respectively in December, March, June and September. Mean hair zinc level in March was significantly different ( rxO.Ol ) from those in December, June and September. A significant difference ( p<0.01 ) was determined in mean alkaline phosphatase levels between completely and incompletely hair shed cattle in March. There was a significant difference ( p<0.05 ) between mean plasma zinc level ( 106.02 ± 2.21 pig/dl ) of Holstein cattle in September and that ( 98.52 ± 2.50 /*g/dl ) of Swiss Brown cattle for the same month. Highly significant differences ( p<0.001 and p<0.01 ) were found to present between mean plasma zinc levels of cattle in lactation period ( 103.47 ± 2.39 jig/dl ) and in dry period ( 121.67 ± 4.51 /*g/dl ) in December and also between mean plasma zinc levels of cattle in lactation period ( 101.44 ± 2.43 /*g/dl ) and in dry period ( 116.47 ± 5.08 pg/dl ) in June. The presence of significant difference ( p<0.05 ) between mean plasma alkaline phosphatase level of cattle in lactation period ( 76.67 ± 7.65 IU/L ) and in dry period ( 106.39 ± 9.82 IU/L ) in December and also between mean plasma alkaline phosphatase level of cattle in lactation period ( 53.11 ± 3.13 IU/L ) and in dry period ( 68.23 ± 7.49 IU/L ) in September was found. A significant difference ( p<0.01 ) was found to present between mean plasma zinc levels of pregnant ( 112.82 ± 2.80 /*g/dl ) and nonpregnant ( 100.96 ± 3.50 }ig/d\ ) cattle in December. A positive correlation was determined between plasma zinc level and the activity of plasma alkaline phosphatase in all 4 months, with being particularly significant ( p<0.01 ) in September.65 This study did not find any clinical signs related to zinc deficiency in Swiss Brown and Holstein cattle in breeding farms of Elazığ and its vicinity. However, when plasma and hair zinc levels were considered all cattle were found to have critical zinc levels of 30.17 % and 46.5 %. On the other hand, plasma zinc concentration of 1.7 % of these cattle was found to have reached almost the level that might show the deficiency signs. As a result, the plasma and hair zinc levels of Swiss Brown and Holstein cattle bred in and around Elazığ show that these animals predispose to the subclinical zinc deficiency. In this regard, these animals are likely to be less productive than expected. Therefore, it has been suggested that the ration should be examined with regard to the level of zinc, and if necessary, a sufficient amount of zinc ought to be added to ration in order to prevent the economic losses arising from subclinical zinc deficiency.
Investigations on the values of blood plasma zinc, alkaline phosphatase and hair zinc of cattle n Elazığ and its vicinity
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Veteriner Hekimliği; Veterinary Medicine